The Effect Of Workload And Work Stress On Employee Performance - Siti Sheila Putri; Rahmad Bahagia (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this study is to find out and analyze workload affecting performance, to find out and analyze work stress affects performance and to find out and analyze workload and work stress on employee performance both partially and simultaneously at PT. Pos Indonesia Medan Post Office. The approach used in this study was an associative approach while the sample that met the criteria for drawing an observation sample was 67 people using a saturated sample, namely all employees at PT. Pos Indonesia Medan Post Office. Data collection techniques in this study used questionnaires, interviews, and documentation studies. The data analysis technique in this study uses Classical Assumption Test, Multiple Linear Regression, Hypothesis Test (t Test and F Test) and Coefficient of Determination. Data management in this study used the SPSS (statistical Package for the Social Sciens) software program version 16.0. The results of this study prove that partially workload affects Employee Performance while Work Stress has an effect on Employee Performance. Simultaneous Workload and Work Stress affect Employee Performance.